The effect of tightening standards on automakers’ non‐compliance - Hu, K; Chopra, S; Chen, Y (SAGE Publications, 2021)
This study investigates how tightening standards can result in greater non‐compliance, especially when market and regulatory interests are misaligned. We confirm a causal relationship that explains the highly publicized auto industry non‐compliance phenomenon where on‐road NOx emissions exceeded standards. Based on a 15‐year on‐road vehicle emissions dataset covering 148,837 vehicles from 42 automakers in the EU, we use regression discontinuity to identify the causal impact of standards tightening on non‐compliance by controlling other confounding factors. Our results suggest that in the absence of effective monitoring, tightening standards directly drives up automakers’ non‐compliance. Furthermore, we find that automakers facing more intense substitution pressure from competitors or with less advanced emissions control technology have a higher non‐compliance rate. Our findings speak to both policymakers as well as managers in the private sector. When setting limit‐based performance goals in situations with conflicting interests and imperfect monitoring, they should anticipate non‐compliance from the regulated parties. Our results suggest that tightening standards in such situations should be accompanied by stricter monitoring or other actions that discourage non‐compliance.